Slam dunk! science projects with basketball - Gardner, Robert, 1929-2017; Shortelle, Dennis (Berkeley Heights, NJ : Enslow Publishers, 2010)
"Presents several science experiments and science project ideas using physics and basketball"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Physics -- Experiments -- Juvenile literature; Science -- Experiments -- Juvenile literature; Basketball -- Juvenile literature; Science projects -- Juvenile literature